Broadband Omnidirectional Nearly Perfect Plasmonic Absorber For Solar Energy Harvesting - Nihal F. F. Areed; Sameh Mohamed El Malt; Salah S. A Obayya (IEEE Photonics Journal)
In this paper, an efficient, broadband, omnidirectional visible plasmonic absorber is presented and numerically simulated using the rigorous three-dimensional finite difference time domain (FDTD) method and the 2-D finite element method. The proposed absorber comprises hollow cylindrical layers of aluminum (Al) and silicon dioxide ( ${\rm{SiO}}_{{2}}$ ). Arranging the geometry and adjusting the dimensions of the cylindrical layers generate localized plasmonic modes at the ${\rm{Al/ SiO}}_{{2}}$ interfaces, as well as inside the gap between two Al layers, and thereby, strong optical confinement in the visible range is allowed. Therefore, the light absorbance of over 93% is observed over the whole visible regime with a relative bandwidth from 0.4 to 0.75 PHz. Further, due to the cylindrical geometry, the absorption is almost independent on the incident angles in a wide range (–90° to 90°). Two elements of the proposed absorber have been employed to function as a nanoantenna for converting the solar energy to electricity. The proposed nanoantenna offers omnidirectional harvesting characteristics with efficient harvesting efficiency that is higher than that of the conventional rectangular dipole nanoantenna by about 38%.